Pemberdayaan Hukum dan Kesehatan Masyarakat di Desa Kota Lintang Bawah Aceh Tamiang - Juliandi, Budi; Husna, Nurul; Annisa, Delia; Rezeki, Dinda Sri; Primanty, Diah Aidil; ‘Ulya, Khairil; Juliadi; Hasbi, Muhammad (LSM Catimore dan Sahabat, 2024)
Abstract Family problems or what is called munakahat are never ending discussion, including stunting, both in terms of unregistered marriages, divorce outside of court, domestic violence, and also programs that have been held by the National Population and Family Planning Agency (BKKBN) to prevent stunting. The aim of this research is to see the decrease and increase in family problems and stunting in lower latitude urban village communities. The research method used in this research is qualitative with a juridical-empirical approach. The research results show that there is an increase and decrease in unregistered marriages, marriages outside the court, and domestic violence, as well as stunting problems in lower latitude urban villages. Keywords: Empowerment, Law, Health